Uninucleate and binucleate spores of Vairimorpha necafrix: pathagenicity to Spodoptera latifascia and sensitivity to ultraviolet radiation - Lima, Maria Goretti Araújo de; Lord, Jeffrey C.; Roberts, Donald W. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to compare binucleate and a mixture of binucleate and uninucleate spores of Vairimorpha necatrix (Protozoa: Microspora) in terms of survival under ultraviolet light and pathogenicity to larvae of Spodoptera latifascia (Lepidoptera: Noctuidae). Larval feeding on cowpea leaflet disks at doses of 3.0 x 104; 1.2 x 104; 7.4 x 10³ and 4.3 x 10³ spores/larvae resulted in LT50s of 16.6, 20.1.23.1, and 29.9 days for binucleate spores and 23.5. 25,9, 28.0, and 38.4 days for the mixture, respectively. The values for the mixture were significantly higher (P < 0.05) than for the binucleates, suggesting that uninucleate spores are less pathogenic to S. latifascia than binucleate spores. The spore viability decreased with the increase of exposure time, in both spores studied. After seven hours of exposure to short wave ultraviolet light, the binucleate spores and the mixed spores were associated with 21% and 20% infection, respectively.